Lived experiences of selected grade seven teachers’ integration of democratic values into their EMS lessons - Koopman, Karen Joy; Laubscher, Abeline Olivier (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
This study investigates the lived experiences of Economic and Management Sciences (EMS) teachers and how they integrate democratic values into their lessons. The study focuses primarily on EMS teachers’ understanding of what democratic values are and how they were implicitly integrated into certain EMS topics. Methodologically, the study employed a Husserlian phenomenological approach to the data-construction process in which interviews and fieldnotes were the main sources of data. This approach assisted the researchers in eliciting rich descriptions of the teachers’ experiences on how they integrate democratic values into Grade 7 EMS lessons. A total of 5 EMS teachers were purposively selected to participate in the study. Theoretically, the study draws on Husserl’s ‘lifeworld’ theory and Heidegger’s interpretive phenomenology with a focus on Dasein, which has been integrated with Karl Maton’s Legitimation Code Theory (LCT). The findings revealed that the teachers all integrated democratic values into their lessons. Their lessons were both rich in semantic gravity (SG+) and semantic density (SD+). From a Heideggerian perspective it showed how these values were cemented in their consciousness as part of their “Dasein” (“being there”) as children. The findings could help expand our understanding of what goes on in the minds of EMS teachers when they teach democratic values
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (3) (2022) Special Issue
Keywords: Economic and Management Sciences; Grade 7; Teachers; Phenomenology; Phenomenology; Teaching; Economic and management sciences -- Study and teaching